Multi-Density Datasets Clustering Using K-Nearest Neighbors and Chebyshev’s Inequality - Bouchemal, Amira; Kimour, Mohamed Tahar (Informatica, 2023)
Density-based clustering techniques are widely used in data mining on various fields. DBSCAN is one of the most popular density-based clustering algorithms, characterized by its ability to discover clusters with different shapes and sizes, and to separate noise and outliers. However, two fundamental limitations are still encountered that is the required input parameter of Eps distance threshold and its inefficiency to cluster datasets with various densities. For overcoming such drawbacks, a statistical based technique is proposed in this work. Specifically, the proposed technique utilizes an appropriate k-nearest neighbor density, based on which it sorts the dataset in ascending order and, using the statistical Chebyshev’s inequality as a suitable means for handling arbitrary distributions, it automatically determines different Eps values for clusters of various densities. Experiments conducted on synthetic and real datasets have demonstrated its efficiency and accuracy. The results indicate its superiority compared with DBSCAN, DPC, and their recently proposed improvements.